Love of Money Behavior, Religiosity, and Ethical Values on the Tendency of Accounting Fraud With Idealism as a Moderating Variable. - Reswari , Anis Arista; Sukma Nirwana, Nihlatul Qudus (Indonesian Journal of Islamic Studies, 2023)
This quantitative study investigates the impact of love of money, religiosity, and ethical values on accounting fraud tendencies, while also examining the moderating role of idealism. Conducted within the finance division of a food and footwear company, the research employs purposive sampling to gather data from 50 respondents through questionnaires, analyzed using the SmartPLS method. The findings reveal that love of money and ethical values significantly affect accounting fraud tendencies, whereas religiosity exerts no such influence. Furthermore, idealism moderates the relationship between ethical values and accounting fraud tendencies, underscoring its potential as a valuable reference point for future research in this domain. Highlights: Impact of Ethical Values: Ethical values play a significant role in influencing accounting fraud tendencies, emphasizing the importance of fostering an ethical corporate culture. Limited Influence of Religiosity: Religiosity is found to have no substantial effect on accounting fraud tendencies, challenging assumptions about its role in shaping financial behavior. Moderating Role of Idealism: Idealism is identified as a critical moderating factor, affecting the relationship between ethical values and accounting fraud tendencies, highlighting its relevance in fraud prevention efforts. Keywords: Accounting Fraud, Love of Money, Religiosity, Ethical Values, Idealism